Distribution system reliability enhancement by using grid upgrading technology - Rashid Zaidan, Majeed (International Journal of Engineering and Technology, 2019)
Losses are essential threat to power system reliability and worthiness; such disturbances are raised form generation plants until destination and end users. Power loss due to load variation is studied in this paper when radial distribution system is considerable; load is arranging among feed-forward nodes and hence losses may be developed due to overload in any particular node. As the radial system is involved, any changing of network topology yields a noticeable improvement on reliability. More topologies are resulted by changing the feeder switching status. IEEE 16 bus-bar radially structured distribution grid is investigated using Matlab software. Results shown that optimum reliability is achieved when node 2, node 4 and node 15 are closed. So far this topology is active, power loss is minimized and voltage profile is improved as compared to seven iterations of different topologies.Â Â